Rates the Ships Must Pay to Deliver the Oil Sludge as an Incentive to Improve Port Waste Green Logistics - Danijela Tuljak-Suban; Valter Suban (Promet - Traffic&Transportation, 2021)
Vessels of the shipping industry produce sludge during the operation of the main engine, various types of auxiliary engines, and the handling of fuel oil on board ships. The sludge can be stored in special tanks and disposed of ashore or burned on board. In the European Union, according to the Port Reception Facilities Directive (EU) 2019/883, ships have to pay a port waste fee for the delivery of ship waste, which is calculated according to the size of the ship. Such an approach does not take into account the capacity of port green waste logistics. In this paper, the case of delivery of ship sludge to ports that are similar in terms of waste logistics capacity is analysed. It is presented as a mathematical game between ships and ports to improve green waste logistics and match the amount of oil sludge that can be discharged from ships to the capacity of ports. The goal of the game is to discourage free-riders, which can occur on both sides, between suppliers and ports. The waste rate can be used as a regulator and incentive that discourages sludge dumping when recycling is not feasible. A model evaluation is proposed using a numerical example.